PENGARUH KUALITAS PRODUK, SALURAN DISTRIBUSI DAN PERSEPSI HARGA TERHADAP KEPUASAN PELANGGAN PADA EKA COFFEE - Candy Junior Herlambang; David Sukardi Kodrat (Jurnal Performa : Jurnal Manajemen dan Start-up Bisnis, 2023)
The purpose of this research is to test and analyze the effect of product quality, distribution channel and price perception on customer satisfaction at Eka Coffee company. This analysis method uses IBM SPSS STATISTIC 22 analysis software with 3 tested hypotheses. The research method that is used in research is quantitative. The population that is used is all Eka Coffee customers from May to November 2020 that amount to 30 customers then take the sample of 30 customers with saturated sample method. The data collection method is done with questionnaire method. The test method that is used is validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, linearity test, multiple linear regression analysis, t test, F test, and determination coefficient test. The results of the research show that product quality not affect significant on customer satisfaction, distribution channel not affect on customer satisfaction and price perception not affect on customer satisfaction.